Peering into the Future of Intelligent Systems: Lessons from the SPRING Program. Issue 3 (4th May 2019) - Culver, Tom; Green, Lee; Redden, Jim
Abstract : Overview: Innovation leaders face the challenge of planning for their organizations' future in a time of technological and economic upheaval; the rapid emergence and proliferation of intelligent systems will be a key factor in that upheaval, and a key technology that organizations must be prepared to manage. A foresight program can help organizations map the challenges and opportunities presented by emerging technologies and serve as a valuable input to organizational strategic planning. IRI and RTI International developed a foresight program for intelligent systems to guide companies in framing, exploring, envisioning, and acting on the impacts intelligent systems may have. Working from an intelligent systems research framework, the program identified 70 key drivers of change and developed three scenarios depicting plausible and thought-provoking visions of the future of intelligent systems. These scenarios highlight critical uncertainties and help innovators challenge conventional notions about how the future might unfold. The steps taken in developing the scenarios can provide the basis for other organizations' use of foresight methodologies to better understand the possible impact of intelligent systems on their strategic goals and objectives.